Analisis Pola Aktivitas Kombong Pada Petani Padi Untuk Meningkatkan Produktivitas Pertanian Yang Berkelanjutan di Kecamatan Malua Kabupaten Enrekang - Irmayani, Irmayani; Nurul Aisyah; Arman, Arman; Nurhaedah, Nurhaedah (Fakultas Pertanian, 2024)
Gotong-royong culture is a form of social activity carried out by society from ancient times to the present. Work togethe culture or Kombong has become a potential that has an important role in increasing productivity of farmers. The purpose of this research is to find out the activity pattern of the combo and the relationship between productivity and combo activity in Dulang village of Malua district of Enrekang. This research uses a kind of descriptive qualitative research method. Data was collected through observations, documentary interviews with samples of 25 people using descriptive data analysis techniques. The results of this study show that the Kombong Activity Pattern in Dulang Village, Malua Prefecture, Enrekang District shows that the perception of the community towards the Combination Activity pattern is very structured from the pattern of land management, agricultural cultivation and harvest patterns carried out jointly involves the alternate division of work between farmers with the aim of making the work easier and more efficient and the public view of Kombongan is very positive as a tradition that strengthens the common and solidarity among the members of the village of Dulang. Relationship between Productivity and Kombong Activity in Dulang Village, Malua Prefecture, Enrekang District shows that the very effective relationship between productivity with Kombongan Activity at Dulang village is proven by energy efficiency and increased farmers income figures proving that there is a relationship between Productive Activity and Kombong Aktivity in Malua Village, Dulang District.